Entrepreneurial marketing and international new ventures : antecedents, elements and outcomes - Kowalik, Izabela (New York : Routledge, 2020)
'The book investigates the entrepreneurial marketing (EM) concept within the broader discipline of international entrepreneurship. The analysis of this concept, and designing a model of EM antecedents, elements, and outcomes that was tested on the basis of empirical studies covering companies from three European countries, explores and develops the field of international marketing and entrepreneurship. The book examines the role of entrepreneurial marketing in the internationalization processes of new ventures and adopts both qualitative and quantitative methods for analyzing the antecedents and characteristics of entrepreneurial marketing, as well as their relationships with internationalization activities and firms' performances. It goes on to show how the application of entrepreneurial marketing may lead to an accelerated internationalization of companies originating from a transition market, as well as the Western-European markets. It addresses these topics with regards to entrepreneurial marketing and management and will be of interest to researchers, academics, managers, entrepreneurs, and students in the fields of international business, international marketing, and entrepreneurship'--
Includes bibliographical references and index.
Keywords: New business enterprises -- Management; Marketing -- Management; International business enterprises -- Management; Export marketing